2016
DOI: 10.1186/s12983-016-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the New World titi monkeys (Callicebus): first appraisal of taxonomy based on molecular evidence

Abstract: BackgroundTiti monkeys, Callicebus, comprise the most species-rich primate genus—34 species are currently recognised, five of them described since 2005. The lack of molecular data for titi monkeys has meant that little is known of their phylogenetic relationships and divergence times. To clarify their evolutionary history, we assembled a large molecular dataset by sequencing 20 nuclear and two mitochondrial loci for 15 species, including representatives from all recognised species groups. Phylogenetic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 75 publications
8
125
0
16
Order By: Relevance
“…Nevertheless, if forest fragmentation occurs at high levels, the dramatic reduction of suitable habitat could result in the isolation of groups [Isabirye-Basuta and Lwanga, 2008], reducing their interactions, and also the rates of territorial calls. Robinson et al [1987] found that groups of titi monkeys (cited as Callicebus moloch , now considered Plecturocebus ornatus following Byrne et al [2016]) with small home ranges (HRs; ≤ 4 ha) tend to emit territorial calls from border areas of their territories, while conspecifics with larger HRs did that from central zones. Theoretically, smaller HRs lead to strong spatial competition, demanding intensive patrolling along territory boundaries where frequent group encounters promote high rates of territorial calls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, if forest fragmentation occurs at high levels, the dramatic reduction of suitable habitat could result in the isolation of groups [Isabirye-Basuta and Lwanga, 2008], reducing their interactions, and also the rates of territorial calls. Robinson et al [1987] found that groups of titi monkeys (cited as Callicebus moloch , now considered Plecturocebus ornatus following Byrne et al [2016]) with small home ranges (HRs; ≤ 4 ha) tend to emit territorial calls from border areas of their territories, while conspecifics with larger HRs did that from central zones. Theoretically, smaller HRs lead to strong spatial competition, demanding intensive patrolling along territory boundaries where frequent group encounters promote high rates of territorial calls.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this correction factor is often unknown, and some studies have deduced or extrapolated call rates from other species [Brockelman and Ali, 1987;Nijman and Menken, 2005;Höing et al, 2013]. For example, the territorial calls of the Beni titi monkey (Plecturocebus modestus) and Olalla brothers' titi monkey (P. olallae) , primates endemic to Bolivia (formerly: Callicebus modestus and C. olallae , respectively [Lönnberg, 1939;Hershkovitz, 1990;Felton et al, 2006;Martinez and Wallace, 2007, 2013Byrne et al, 2016]), both categorized as Endangered [Veiga et al, 2008a, b], were used to assess population density and size, but due to a lack of behavioural information the correction factor was estimated from short observations [López-Strauss, 2008;López-Strauss and Wallace, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Plecturocebus pallescens Thomas 1907 X TXNM: as Callicebus donacophilus in Myers et al (2002), species clarification updated in Groves (2005), and family and generic clarification updated by Byrne et al (2016).…”
Section: Txnm: Family and Subfamily Clarification By Rylands And Mittmentioning
confidence: 99%
“…Fossil and molecular evidence indicate that the three major clades of modern platyrrhines were established in the Miocene (Kay 2015), but as in other groups of primates, further divergence subsequently occurred. In titi monkeys, for example, the Pliocene saw the split between the donacophilus and moloch groups (Byrne et al 2016). The Pliocene also witnessed an important dispersal of monkeys northwards into Central America, made possible by the connection through the Isthmus of Panama between the continents of South and North America around 3.5 Ma (Kay 2015).…”
Section: New World Monkeysmentioning
confidence: 99%